Study Patient Satisfaction with Covid-19 Self-Isolation At-Home Services Monitoring - Lubna, Lubna; Boerman, Baequni; Salsabila Samara, Shafira (Universitas Nahdlatul Ulama Surabaya, 2024)
The extent of COVID-19 transmission in Jakarta has overwhelmed healthcare facilities, making it challenging to accommodate all incoming patients. Jakarta initiated the COVID-19 Self-Isolation Patient Monitoring Program at each Community Health Center (Puskesmas). This crucial initiative was implemented during the peak pandemic period from March to May 2022. To assess the program's success, 100 respondents were selected through purposive sampling to participate in this research. The objective of this study was to evaluate patient satisfaction and explore the relationship between patient characteristics and the five dimensions of service quality based on the SERVQUAL model. The analysis revealed an overall patient satisfaction rate of 88%. Additionally, through Chi-square analysis, the findings highlighted a significant relationship between employment status (P-value = 0.017) and service quality dimensions, including tangibility, reliability, responsiveness, assurance, and empathy (each with a P-value = 0.001) about patient satisfaction. However, lower satisfaction levels were identified in specific areas, such as the daily monitoring of a patient's conditions during self-isolation (75%), the availability of free swab tests at the Puskesmas (77%), and the prioritization of patient care during self-isolation (78%). This study outlines the program's strengths and areas that require service improvement to enhance patient satisfaction.